Shear resistance behavior of partially composite Steel-Concrete-Steel sandwich beams considering bond-slip effect. (1st May 2020) - Zhang, Wei; Huang, Zhenyu; Fu, Zhanxia; Qian, Xudong; Zhou, Yingwu; Sui, Lili
Highlights: We report an experimental study on shear behaviour of partially composite sandwich beams. We examine the effect of bond-slip on the failure mechanism and shear resistance of sandwich beams. We investigate the effect of span-to-depth ratio, steel contribution ratio on shear behaviour. We investigate the effect of connection type, spacing between shear connectors on shear behaviour. We propose a new model to integrate the effect of bond-slip to estimate the shear resistance of sandwich beams. Abstract: This study develops a new steel-concrete-steel (SCS) sandwich beam with hybrid shear connectors comprising both J-hooks and overlapped headed studs. For partially composite SCS sandwich beams, bond-slip is a critical factor influencing the transverse shear resistance of the beam. Thus, this study examines the effect of the degree of composite action and the mechanism of such sandwich beams by testing eight SCS sandwich beams with different shear span-to-depth ratios, steel contribution ratios, types of shear connectors, and spacing of shear connectors. The parametric study thoroughly discusses the effects of these variables on the beam failure modes and beam shear resistance. Based on existing design models, this paper proposes a new analytical model that considers the bond-slip effect to predict the ultimate resistance of SCS sandwich beams. The new model includes contributions from the concrete, shear connectors, and steel plates. Available test data from 57 specimens successfully validated the proposed model.